Meningkatkan Hasil Belajar Peserta Didik Melalui Model Pembelajaran Cooperative Script Dengan Teknik Merangkum - Dewi Asiah (Universitas Mathla'ul Anwar Banten, 2020)
Teaching and learning activities in the classroom are a major part of the educational process. Learning and teaching poses that are expected by the world of education will not be realized properly if there is no harmony between educators, students, teaching materials and the environment. The process of teaching and learning activities at SMAN 5 Pandeglang is not optimal. This is caused by a lack of preparation, motivation and student learning methods. This research is tested for; (1) Describing the cooperative script model procedure with summarizing techniques in improving student learning outcomes. (2) Shows the success of implementing the cooperative script model with summarizing techniques in improving student learning outcomes. This research is a classroom action research carried out in the form of implementing a model design in two cycles carried out in four stages which include; (1) planning, (2) implementation, (3) observation, and (4) reflection. The results of this study indicate that there is an increase in student learning outcomes using a cooperative script model with summarizing techniques.